A Novel Rat Model of Mild Pulmonary Hypertension Associated with Pulmonary Venous Congestion Induced by Left Pulmonary Vein Banding - Münks, Jonas; Yogeswaran, Athiththan; Antoine, Tobiah Kevin; Blumrich, Leonhard Anton; Dorfmüller, Peter; Ghofrani, Hossein Ardeschir; Assmus, Birgit; Schermuly, Ralph Theo; Sydykov, Akylbek; Justus Liebig University Giessen (My University, 2024)
Pulmonary hypertension (PH) associated with left heart disease (PH-LHD) is the most common form of PH. In PH-LHD, changes in the pulmonary vasculature are assumed to be mainly caused by pulmonary venous congestion. However, the underlying mechanisms of this form of PH are poorly understood. We aimed to establish a model of PH associated with pulmonary venous congestion. Wistar–Kyoto rats underwent partial occlusion of the left pulmonary vein to induce pulmonary venous congestion or sham surgery and were assessed at various time points post-surgery (3, 6, 9, 12 weeks). In vivo cardiopulmonary phenotyping was performed by using echocardiography along with heart catheterization. Histomorphometry methods were used to assess pulmonary vascular remodeling (e.g., wall thickness, degree of muscularization). Left pulmonary vein banding (PVB) resulted in mildly elevated right ventricular systolic pressure and moderate right ventricular hypertrophy. In PVB rats, small- and medium-sized pulmonary vessels in the left lung were characterized by increased wall thickness and muscularization. Taken together, our data demonstrate that left PVB-induced pulmonary venous congestion is associated with pulmonary vascular remodeling and mild PH.
Keywords: ddc:610